(untitled) (Research, Society and Development, 2022)
MDF began to be produced in Brazil at the end of the 90’s and since then the market for this product has been expanding in the country, due to the creation of new production units, as well as the search for new sources of technology and modernization of the Brazilian industry, contributing to socioeconomic development. The present research analyzed the competitive performance of the Brazilian MDF industry and of the four largest exporters of the product in the world (Germany, Belgium, Thailand and China), between the period of 1995 and 2020, using the indices of Revealed Comparative Advantage, Coverage Rate, Strengths, Neutrals and Weaknesses and Relative Market Position. It was found that Brazil was competitive from 2015 and over the years has gained competitiveness in the international product market. Germany, on the other hand, was the most competitive country followed by Belgium, Thailand and China according to the estimated indicators.